How Are We Doing?—The Experience of the Merton Home Treatment Team in Gathering Real-Time Feedback and the Impact Upon Service Provision. (December 2017) - Rutherford, Michael D; Akram, A
Aims and Method: To discuss the methods involved in gathering real-time feedback (RTF) by a London Home Treatment Team. We hypothesized that RTF would lead to changes in service provision and improvements in patient and carer feedback. Patients were invited to provide RTF on discharge. Quantitative and qualitative data were collected and analyzed centrally by the Trust before being disseminated to the team and changes made based upon the results. Quantitative feedback on the team's performance in the first 6 months of RTF use was compared against data from the 6 months prior to March 2015 using 2-tailed Z tests. Results: There were significant improvements in feedback around the team visiting at the agreed times ( P = .0069) and patients feeling that they had been involved in treatment decisions ( P = .0371). Clinical Implications: Real-time feedback is a potentially valuable method for obtaining patient feedback and can result in service improvements if used appropriately.